Contribution of Optical Coherence Tomography in the Diagnosis and Follow-up of Primary Open-Angle Glaucoma - AIGBE, Nestor; ADOU, Nath; ALFA BIO ISSIFOU, Amadou; ABOUKI, Chakiratou Olaïdé Adoukê; ALAMOU, SOULÉ; ODOULAMI-YEHOUESSI, Lisette (My University, 2024)
Abstract Objective: To study the contribution of OCT in the diagnosis and follow-up of POAG at the ophthalmological clinic of the University Hospital Center in the Suru Lere area and at the ophthalmological clinic of HIA - CHU. Method: This is a descriptive and analytical study, retrospective over a period of 7 years from 1st January 2015 to 31st December 2021. Results: We identified a total of 30 patients, i.e. 60 glaucomatous eyes, in whom at least two OCTs were performed. The average age of the patients was 51.23 ± 12.16 years with extreme values of 23 to 72 years. In our series, 17 patients were male (56.65%), i.e. an M/F sex ratio of 1.30, employees were in the majority and represented 66.67% of patients, patients with no history represented 60 %. The main risk factors were hypertension, HT0 with respectively 20%, 13.33%. Visual loss was the main reason for consultation, 56.67%. The average cup/disc ratios on clinical examination of the papilla are respectively 0.57 ± 0.19 on the right and 0.58 ±0.18 on the left. In our series, the means of the three OCTs for the C/D ratios were established respectively at 0.70, 0.71 and 0.62 for the right eye and respectively 0.70, 0.71 and 0.65 for the left eye. Regarding the mean of the per papillary RNFL, the means of the three OCTs are respectively 86.27; 83.93; 86.29 for the must eye and 89.20 respectively; 83.47; 85.07 for the left eye. For the ganglion cell complex the results were respectively 85.63; 81.73, 71.71 for the right eye and 86.07 respectively; 81.23 and 71.86 for the left eye. There was a significant correlation between fundoscopic and tomographic vertical C/D ratios. Conclusion: It appears from this work that OCT is an essential material examination and plays an important role in both the diagnosis and the follow-up of glaucomatous disease. Keywords: Glaucoma; Diagnosis; Progression; Tomography
Keywords: Keywords: Glaucoma; Diagnosis; Progression; Tomography